EFFECT OF EMPLOYEE MOTIVATION ON ORGANIZATIONAL PERFORMANCE (CASE: MOGADISHU MUNICIPALITY) - Hassan, Mohamed Ibrahim; Owuor, Evelyn Datche (International Journal For Research In Business, Management And Accounting, 2017)
The purpose of this study was to determine the effect of employee on organizational performance. The specific objectives were: to establish the effect of motivational tools on organizational performance in Mogadishu Local Government/Banadir regional administration MLG/BRA. The study utilized both quantitative and qualitative approaches design based on descriptive in nature. It was used both approaches that it was based on variables with numbers and analyzed with statistical procedures using descriptive statistics (Creswell, 2003). Qualitative research was used because it reveals valuable attitudes and perspectives that can be hardly accessed and obtaining data expressed in non-numerical terms (Amin, 2005) while Quantitative research was used on numerical data, measurable variables. The study made use of a survey study research design using of administered questionnaires. The target population was Somali employees especially those who work in government offices. The study targeted MLG/BRA staff with unit of enumeration consisting of 28 directors of departments (Managerial Level), 36 head of sections (Tactical Staff) and normal staff of 52 (Operational Staff), making a total target population of 168 respondents. The study sampled 22 directors of departments, 28 head of sections and 40 of normal staff 90 respondents. The data was analyzed using SPSS Version 20 The key finding was that there is a strong positive relationship between the Pay Schemes and organizational performance. There is a strong positive relationship between the reward system and organizational performance MLG/BRA. There is positive relationship between the job security and organizational performance, in while there is less affect between promotion and organizational performance that results poor performance in MLG/BRA.